Recent development of economic sociology in Korea - Kyungmin Baek (economic sociology. perspectives and conversations, 2021)
Economic sociology in Korea has been growing in earnest since the early 1990s. Scholars influenced by Anglo-American sociology began to criticize the logic of neoclassical economics, which presupposed an atomized independent actor who pursues utility maximization. They claim that social actors are embedded in various social relationships. As a result, social institutions and limited human rationality play an important role in shaping a decision for economic behavior. The scope of their research in Korea has extended to the study of the state, organization, and individual behaviors, and the research outputs have greatly contributed to the analysis of Korean society. The studies of economic sociology in Korea can be divided into three categories: state, organization, and individual. In this article, I examine how economic sociology has been developing recently in each area. To this end, I focus on the discussion in academic journals published since the late 1990s in Korean. (...)
Keywords: 300